Correlation of insulin resistance with neutrophil to lymphocyte ratio and serum ferritin in male patients of metabolic syndrome - Uzma Zafar; Ali, Zaima; Khaliq, Saba; Lone, Khalid Pervaiz (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the correlation of insulin resistance with neutrophil-to-lymphocyte ratio and serum ferritin, and to evaluate whether NLR and serum ferritin can predict insulin resistance in metabolic syndrome. Method: The cross-sectional analytical study was conducted at the University of Health Sciences, Lahore, Pakistan, from July 2016 to 2019, and comprised male patients of metabolic syndrome and healthy controls. The correlation involving insulin resistance, serum ferritin and neutrophil-to-lymphocyte ratio was determined. Data was analysed using SPSS 22. Results: Of the 210 subjects, 160(76.2%) were cases with a median age of 45 years (interquartile range: 39-50 years), and 50(23.8%) were controls with a median age of 41 years (interquartile range: 35-50 years). Serum ferritin, alanine aminotransferase, total neutrophil count, lymphocyte count and neutrophil-to-lymphocyte ratio were significantly higher among the cases than the controls (p<0.05). Significant positive correlation of insulin resistance was observed with serum ferritin and neutrophil-to-lymphocyte ratio (p<0.05)) among the cases. Neutrophil-to-lymphocyte ratio significantly predicted insulin resistance among the cases (p<0.05). Conclusion: Neutrophil-to-lymphocyte ratio was fund to be a significant predictor of insulin resistance in metabolic syndrome. Key Words: Neutrophil to lymphocyte ratio, Ferritin, Type 2 diabetes. Insulin resistance. Continue...